THE RATIONALE FOR THE USE OF TWO-PHASE SWITCHES FOR THREE-PHASE CONNECTIONS OF DISTRIBUTIVE DEVICE 27.5 KV - Sheika, Yu. Ya. (Science and Transport Progress, 2009)
On the basis of materials of scientists of Moscow and Petersburg State Universities of C Ways and NIIEFAENERGO Ltd.» the author of this article with additions has considered a practical possibility of us bipolar switches on three-phase connections of distributive device 27,5 кV.